How to improve the well-being of patients in cardiac rehabilitation? A contribution of psychological treatments - Crepaldi, Maura; Zambetti, Elisa; Lanfranchi, Fiorella; Zenoni, Emanuela; Bariletti, Irene; Quarenghi, Francesco; Viscardi, Luigina; Rizzola, Ginevra; Regazzoni, Valentina; Bigoni, Alessandra; Brivio, Francesca; Anselmi Kaiser, Massimiliano; et al. (Frontiers in Psychology, 2025)
IntroductionThe relationship between psychological factors and cardiovascular disease (CVD) has been extensively studied, with a focus on predictive factors and patients’ responses in the acute and chronic phases. However, less is known about the impact of specific psychological treatments on the psychological status of patients in cardiovascular rehabilitation.MethodsThis study compares anxiety, depression and illness perception in patients with different CVD at three-time points: baseline (T0), end of the rehabilitation program (T1), and 3 months later (T2). One hundred and eighty-one patients in cardiovascular rehabilitation participated at three psychological treatments: psychoeducational intervention group, progressive muscle relaxation training with Jacobson’s technique and imaginative stabilization techniques, and individual counseling. The study included patients with Acute Coronary Syndrome (ACS), heart failure (HF), or undergoing cardiac surgery (CS), undergoing cardiovascular rehabilitation at ASST Bergamo Est between January and August 2023. Levels of anxiety, depression, and illness perception were measured by HADS and Brief-IPQ.ResultsSignificant differences were observed between T0, T1, and T2 in the three psychological treatments, with individual counseling showing the greatest improvements in anxiety, depression, and illness perception.DiscussionThe study shows that individual counseling significantly reduces the levels of depression and anxiety, while promoting a healthier perception of the disease in comparison with the other two psychological treatments offered. This process is critical to improving the psychological well-being of patients, and these results could be useful to better address health care policies.